Development of a sustainable and antibacterial food packaging material based in a biopolymeric multilayer system composed by polylactic acid, chitosan, cellulose nanocrystals and ethyl lauroyl arginate. (April 2023) - Patiño Vidal, C.; Luzi, Francesca; Puglia, Debora; López-Carballo, Gracia; Rojas, Adrián; Galotto, María José; López de Dicastillo, C.
Abstract: Biodegradable packaging materials with antimicrobial properties are main key for developing sustainable active packages able to protect different foodstuff. Thus, the aim of this research was developing a biopolymeric and antibacterial packaging material with a trilayer structure through the combination of extrusion, electrospinning and coating techniques. This trilayer system was composed by a support extruded layer of polylactic acid (PLA), an intermediate PLA electrospun layer loaded with ethyl lauroyl arginate (LAE) and cellulose nanocrystals (CNC), and a third inner chitosan coating. Morphological, wettability, antibacterial and disintegrability properties of this material were evaluated. The morphological surface analysis evidenced the heterogeneity of the chitosan coating over the electrospun PLA layer, and this effect affected negatively the evaluation of wettability of this trilayer material. Antibacterial assays evidenced a fast and strong bactericidal effect against Gram(+) and (−) bacteria that maintained this activity for 15 days. Finally, the biodegradable properties of different layers favored the disintegration of developed trilayer material at 21 days under composting conditions. Graphical Abstract: ga1 Highlights: The combination of extrusion, coaxial electrospining and coating techniques was applied. An antibacterial biodegradable and trilayer food packaging material was obtained. The trilayer material exhibited a strong bactericidal activity for 15 days. The trilayer material was biodegraded under composting conditions after 21 days.